2022
DOI: 10.5014/ajot.2022.049324
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Therapy and the IMPACT Act: Part 2. A Systematic Review of Evidence for Functional Status, Medication Reconciliation, and Skin Integrity Interventions

Abstract: Importance: Interventions that promote function, medication reconciliation, and skin integrity assist occupational therapy practitioners in demonstrating professional value, improving quality, and reducing health care costs. Objective: In this systematic review, we focus on three outcome areas of the Improving Medicare Post-Acute Care Transformation (IMPACT) Act of 2014: functional status, medication reconciliation, and skin integrity. Data Sources: We conducted a search of the li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Lockwood and Porter (2022) conducted a metaanalysis and found low-quality evidence that occupational therapy reduced 1-mo readmission rates among hospitalized adult clients compared with standard care. Two review articles (Feldhacker et al, 2022;Molitor et al, 2022) describe how occupational therapy interventions can improve client outcomes in areas aligned with the Improving Medicare Post-Acute Care Transformation (IMPACT) Act of 2014 (Pub. L. 113-185).…”
Section: Quality Of Occupational Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Lockwood and Porter (2022) conducted a metaanalysis and found low-quality evidence that occupational therapy reduced 1-mo readmission rates among hospitalized adult clients compared with standard care. Two review articles (Feldhacker et al, 2022;Molitor et al, 2022) describe how occupational therapy interventions can improve client outcomes in areas aligned with the Improving Medicare Post-Acute Care Transformation (IMPACT) Act of 2014 (Pub. L. 113-185).…”
Section: Quality Of Occupational Therapymentioning
confidence: 99%
“…L. 113-185). These reviews found mixed evidence for readmission prevention across chronic conditions (Molitor et al, 2022) and low strength of evidence to support occupational therapy interventions to reduce pressure ulcers or promote skin integrity (Feldhacker et al, 2022) This special issue also includes three articles consisting of secondary data analyses to examine relationships between occupational therapy care and quality outcomes. Kubiak and Sklar (2022) found that clients with spinal cord injury who exercised monthly had fewer hospital readmissions during the first year after discharge from inpatient rehabilitation than those who did not exercise.…”
Section: Quality Of Occupational Therapymentioning
confidence: 99%